Productivity, acylsugar concentrations and resistance to the two-spotted spider mite in genotypes of salad tomatoes - Joicy V. M. Peixoto; Ana L. A. Ribeiro; Gabriel M. Maciel; Camila S. de Oliveira; Rafael R. Finzi; Emmerson R. de Moraes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to characterize genotypes of the salad-type tomato with a determinate growth habit and select genotypes resistant to the two-spotted spider mite for higher productivity and fruit quality. The experiment was conducted at the Horticultural Experimental Station (18°42’43.19” S and 47°29’55.8” W, 873 m altitude) of the Universidade Federal de Uberlândia (UFU), Monte Carmelo campus, from January to June 2018. The experimental design was in randomized blocks containing 16 treatments [12 populations of the F3RC2 generation and four controls: two commercial cultivars (Santa Clara and Rio Grande), the recurrent parent (UFU-057) and the wild species Solanum pennellii (LA-716)] with three repetitions. The accessions UFU-057F3RC210#3.6.1 and UFU-057F3RC213#2.1.2 have high potential for genetic improvement regarding resistance to the two-spotted spider mite. The genotypes UFU-13#4.4.1, UFU-7#4.7.1, UFU-7#4.3.2, UFU-13#2.5.2 and UFU-13#2.1.3 present higher acylsugar concentrations than S. pennellii, in addition to higher productivity and number of fruits per plant. It is suggested to explore combinations between those genotypes previously described with UFU-8#2.4.1 to obtain hybrids with high acylsugar concentrations, two-spotted spider mite resistance, high productivity and increased fruit mass.